An Evaluation of Remittance Inflows Through Islamic Banks in Bangladesh - Md. Riazul Haque (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to explore the role of Islamic banks in managing remittance inflows in Bangladesh, focusing on their contribution to economic stability and financial inclusion. Theoretical framework: This study is based on Islamic economic and financial development theory, which emphasizes the role of Islamic financial institutions in supporting economic growth through the principles of sharia compliance, distribution fairness, and operational efficiency in financial transactions. Literature review: The literature review includes data and publications from Bangladesh banks, Islamic bank reports, academic journals, and previous articles, as well as global data sources such as the World Bank, which highlights the dynamics of remittances and the role of Islamic financial institutions in the macroeconomic context of Bangladesh. Methods: This study uses secondary data from three base quarters (October–December 2018, 2020, and 2022), which are then compared with the previous quarter and the same quarter of the previous year, to analyze the growth of Islamic bank branches, remittance market share, and their operational strength. Results: The results of the study show that Islamic banks, especially Islami Bank Bangladesh Limited, dominate the remittance market, followed by Al-Arafah Islami Bank Limited. Despite the growth, these banks also face some operational challenges that need to be addressed. Implications: These findings provide important implications for policymakers and the Islamic banking industry, namely the need to strengthen infrastructure and operational strategies to increase remittance flows through Islamic channels to promote national economic stability. Novelty: The novelty of this study lies in its cross-quarter comparative approach and specific focus on the contribution of Islamic banks in remittances, which has not been systematically studied in the context of Bangladesh.